Investigating the effectiveness of emotional regulation techniques along with drug therapy on reducing blood pressure, anxiety symptoms, depression and hostility in patients with hypertension compared to drug therapy alone - vafaei , Ali; Masjedi Arani , Abbas; Bakhtiary , Maryam; Ghadiani , Mohammad Hassan; Karimi , Reza (Researcher Bulletin of Medical Sciences, 2020)
Objective: Blood pressure-related diseases are the most influenced by psychological factors. The present study was done with the aim of investigating the effectiveness of emotional regulation techniques along with drug therapy on blood pressure reduction, anxiety symptoms, depression and hostility in patients with hypertension compared to drug therapy alone. Materials and Methods: The present study is a quasi-experimental study with pre-test design, post-test design and control group. The population of this study was men and women between the age of 20 to 70 years with hypertension and resident in Tehran province in 2019. Among patients with hypertension referred to Ayatollah Taleghani Training Center Clinic, 30 persons were selected accessibly and were randomly assigned to experimental and control groups. The intervention program of cognitive emotion regulation techniques training was done during 8 sessions in the experimental group. The instruments used in this research were Hospital Anxiety and Depression Scale (HADS) and Spielberger’s State-Trait Anger Expression inventory (STAXI). Results: Analysis of covariance showed that there was a significant difference between the experimental and control groups after the intervention in the level of blood pressure, anxiety, depression and total anger expression index at p <0.05 level. Effect size was 0.39, 0.26, 0.21, and 0.21 in depression, anxiety, blood pressure, and total anger expression index, respectively. Conclusion: Specialists in cardiovascular diseases and health psychology area can employ cognitive emotion regulation techniques to improve the physical and psychological problems of individuals with hypertension including blood pressure, anxiety, depression and anger